A Method To Detect Low Levels of Enteric Viruses in Contaminated Oysters - Shieh, Y.-S. Carol (American Society for Microbiology, 1999)
Direct isolation and identification of pathogenic viruses from oysters implicated in gastroenteritis outbreaks are hampered by inefficient methods for recovering viruses, naturally occurring PCR inhibitors, and low levels of virus contamination. In this study we focused on developing rapid and efficient oyster-processing procedures that can be used for sensitive PCR detection of viruses in raw oysters. Poliovirus type 3 (PV3) Sabin strain was used to evaluate the efficacy of virus recovery and the removal of PCR inhibitors during oyster-processing procedures. These procedures included elution, polyethylene glycol precipitation, solvent extraction, and RNA extraction. Acid adsorption-elution in which glycine buffer (pH 7.5) was used was found to retain fewer inhibitors than direct elution in which glycine buffer (pH 9.5) was used. RNA extraction in which a silica gel membrane was used was more effective than single-step RNA precipitation for removing additional nonspecific PCR inhibitors. The final 10-μl volume of RNA concentrates obtained from 2 g of oyster tissue (concentration factor, 200-fold) was satisfactory for efficient reverse transcription-PCR detection of virus. The overall detection sensitivity of our method was 1 PFU/g of oyster tissue initially seeded with PV3. The method was utilized to investigate a 1998 gastroenteritis outbreak in California in which contaminated oysters were the suspected disease transmission vehicle. A genogroup II Norwalk-like virus was found in two of three recalled oyster samples linked by tags to the harvest dates and areas associated with the majority of cases. The method described here improves the response to outbreaks and can be used for rapid and sensitive detection of viral agents in outbreak-implicated oysters.